Optimasi Komposisi Pakan Ternak Sapi Menggunakan Algoritme Genetika - Simulated Annealing - Akhmad Syururi; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Beef consumption in Indonesia keeps increasing, but the increase has not been balanced with the addition of an adequate production. The rate of population increase beef cattle is relatively slow, 4.23% in 2007. The productivity of the livestock affected by the feed factors, management and breeding. The problem often encountered breeders is the availability of feed, which feed given to livestock contain nutrients that are low so will affect the availability of feed and digestibility of nutrients that impact low produkt ivitas cattle. Based on cases occurs, then the system is built on this research is